PENGARUH KURS DOLAR AS DAN INFLASI TERHADAP DANA PIHAK KETIGA (DPK) PADA BANK NAGARI SYARIAH CABANG BATUSANGKAR - Elmiliyani Wahyuni; Yeni Melia; Meria Ulfa (UIN Mahmud Yunus Batusangkar, 2021)
This study aims to analyze and determine the effect of the US Dollar Exchange Rate and Inflation on Third Party Funds (TPF) at Bank Nagari Syariah Batusangkar Branch for the period 2013-2018. The type of research used in this research is field research with quantitative research methods using a descriptive approach, and using eviews analysis tools with multiple regression and using the Ordinary Least Square (OLS) estimation method. The results of this study indicate that the US Dollar exchange rate variable with a coefficient value (8.141176), the probability value (0.0332) has a positive and significant effect on Third Party Funds (TPF), the inflation variable has a negative and insignificant effect on Third Party Funds (TPF) with a coefficient value ( -0.697542) probability value (0.1019) while the variable US dollar exchange rate and inflation together have a positive and significant effect on third party funds using the Ordinary Least Square (OLS) method, the F-statistic value is 31.98483 with a probability of 0.009481.